2019
DOI: 10.1177/0333102419833076
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation for primary headache disorders: An anatomical review to explain a clinical phenomenon

Abstract: Background Non-invasive stimulation of the vagus nerve has been proposed as a new neuromodulation therapy to treat primary headache disorders, as the vagus nerve is hypothesized to modulate the headache pain pathways in the brain. Vagus nerve stimulation can be performed by placing an electrode on the ear to stimulate the tragus nerve, which contains about 1% of the vagus fibers. Non-invasive vagus nerve stimulation (nVNS) conventionally refers to stimulation of the cervical branch of the vagus nerve, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 120 publications
(187 reference statements)
0
30
0
Order By: Relevance
“…The spinal trigeminal nucleus incorporates sensory information from all three branches of the trigeminal nerve in addition to the facial, glossopharyngeal, and vagus nerves [39]. Extensive interconnections are found among the spinal nucleus of the trigeminal nerve and the solitary nucleus, ambiguous nucleus, and dorsal motor nucleus [40]. A functional MRI study demonstrated that the stimulation of the sensory auricular branch of the vagus nerve evokes extensive activities in brainstem regions, including the solitary nucleus, spinal trigeminal nucleus, and other areas [41].…”
Section: Anatomy and Physiology Of The Brainstemmentioning
confidence: 99%
“…The spinal trigeminal nucleus incorporates sensory information from all three branches of the trigeminal nerve in addition to the facial, glossopharyngeal, and vagus nerves [39]. Extensive interconnections are found among the spinal nucleus of the trigeminal nerve and the solitary nucleus, ambiguous nucleus, and dorsal motor nucleus [40]. A functional MRI study demonstrated that the stimulation of the sensory auricular branch of the vagus nerve evokes extensive activities in brainstem regions, including the solitary nucleus, spinal trigeminal nucleus, and other areas [41].…”
Section: Anatomy and Physiology Of The Brainstemmentioning
confidence: 99%
“…The mechanism by which triptans function to block trigeminal pain is thought to involve inhibiting the release of calcitonin-gene related peptide (CGRP) and other pro-inflammatory molecules from peripheral and central terminals of the trigeminal nerve as well from the cell body within the ganglion (12). In contrast, the inhibitory effect of nVNS as an acute migraine treatment is proposed to promote multiple distinct cellular changes and pathways within the brain and spinal cord to facilitate descending pain modulation (13). The descending inhibitory pathway is known to involve activation of 5-HT3 and 5-HT7 receptors on inhibitory interneurons that stimulates release of glycine and GABA, which act as inhibitory neurotransmitters of primary or secondary trigeminal nociceptors (14).…”
Section: Introductionmentioning
confidence: 99%
“…Even though no clear mechanism of action is known, a multifactorial effect has been proposed [7]. Vagal neuromodulation has been hypothesized to modulate pain pathways of headache [8].…”
Section: Mechanism Of Actionmentioning
confidence: 99%